If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -3 = 9x + 6 Reorder the terms: -3 + 12x = 9x + 6 Reorder the terms: -3 + 12x = 6 + 9x Solving -3 + 12x = 6 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + 12x + -9x = 6 + 9x + -9x Combine like terms: 12x + -9x = 3x -3 + 3x = 6 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + 3x = 6 + 0 -3 + 3x = 6 Add '3' to each side of the equation. -3 + 3 + 3x = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 6 + 3 3x = 6 + 3 Combine like terms: 6 + 3 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 0=x^2-8x+2 | | 8r+8s-7(7r-7s)= | | x^2-63=0 | | 5n-2(2-n)=-7 | | x+4x=12 | | x(x+5)=66 | | 8x+5y=(-23) | | 3x+8x=88 | | -5(x+2)=5(2x+1) | | x=14-4y | | 8(5x-2)=104 | | 6(7-u)=3(u+4) | | lx-2l-2=7 | | 5n(n-2)=-11 | | 2y+2=18 | | lx-4l=4 | | 3(x+6)=-12 | | 4(x+8)=24 | | 4x+2y=(-16) | | 2(x-2)=-16 | | 3x+5y=(-26) | | 2(x-6)=-6 | | 6x-7y=(-15) | | 9x-y=81 | | 2(x+5)=-6 | | 2d+5=8d+2 | | 2(x+4)=0 | | j+-1=-2 | | -(5w+u)+3(3u+3w)= | | 4(x-7)=-32 | | ar+2=3R-6t | | 9=0.5*4h+1 |